A review of direct torque control development in various multilevel inverter applications - Siti Azura Ahmad Tarusan; Auzani Jidin; Mohd Luqman Mohd Jamil‬; Kasrul Abdul Karim; Tole Sutikno (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Multilevel inverter (MLI) is commonly utilized in direct torque control (DTC) for medium and high power applications. The additional voltage vectors generated by MLI can be manipulated to achieve the optimal selection for the inverter switching states in the DTC control systems. Previously, a review of DTC which focused more on the two-level inverter for induction motor as well as a review of the multilevel converter in industrial applications had been implemented individually. However, a review on DTC development in MLI was insufficient in both papers. Therefore, this paper aims to give a comprehensive review of the improvement of DTC via various MLI applications. It is reviewed according to the applicable multilevel inverter topologies in the DTC system. The comparison of DTC by using conventional and multilevel inverter is synthesized. Thus, this review paper will hopefully lead researchers in further research activities actively.